(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
The European humanitarian and migration crisis created by the mass influx of migrants into the European Union that began in 2015 opened up many issues and areas that have not been systematically discussed. The area of irregular entry is certainly one of the most important, precisely because of the legal gaps in the application of the Dublin III Regulation. Recently, the question of irregular entry came before the Court of Justice of the European Union (CJEU) in two cases brought by Slovenia and Austria, whose outcomes have significant consequences for the Republic of Croatia. In the Court’s opinion, admission of third-country nationals in the Member State, with the intention of transferring to another Member State to seek international protection, is considered irregular entry, even in emergencies such as the mass influx of migrants to the state border. Member States receiving a third-country national on their territory shall ensure that all conditions for legitimate entry are met. Without legal preconditions for entry, legitimate residence on the territory of the country of first entry or legitimate transit to another Member State is not possible. The passage of third-country nationals from the Republic of Croatia for humanitarian reasons has resulted in irregular migration because requirements for entry into the state territory were not met. Within these judgments, the CJEU has discussed issues relating to the presumption of lawful entry into the territory of the European Union and the issue of the treatment of a Member State in which a third-country national has first entered. The importance of the CJEU decision is in the fact that it clarifies that the mechanism established by the Dublin III Regulation must inevitably apply, even in exceptional circumstances. The established form of action will certainly be of great importance in the further treatment of Member States because the inflow of migrants to the external borders of the European Union is still expected. This paper will analyse the legal framework regulating the issue of irregular entry and the protection of external borders of the European Union and the main arguments of the CJEU, as well as the opinion of the Advocate General, which was opposing the opinion of the CJEU. The impact of such a Court decision will be critically analysed in this paper as well.